A Spatially Resolved Dark- versus Light-Zone Microenvironment Signature Subdivides Germinal Center-Related Aggressive B Cell Lymphomas - Claudio Tripodo; Federica Zanardi; Fabio Iannelli; Saveria Mazzara; Mariella Vegliante; Gaia Morello; Arianna Di Napoli; Alessandro Mangogna; Fabio Facchetti; Sabina Sangaletti; Claudia Chiodoni; Alison VanShoiack; et al. (iScience, 2020)
Summary: We applied digital spatial profiling for 87 immune and stromal genes to lymph node germinal center (GC) dark- and light-zone (DZ/LZ) regions of interest to obtain a differential signature of these two distinct microenvironments. The spatially resolved 53-genes signature, comprising key genes of the DZ mutational machinery and LZ immune and mesenchymal milieu, was applied to the transcriptomes of 543 GC-related diffuse large B cell lymphomas and double-hit (DH) lymphomas. According to the DZ/LZ signature, the GC-related lymphomas were sub-classified into two clusters. The subgroups differed in the distribution of DH cases and survival, with most DH displaying a distinct DZ-like profile. The clustering analysis was also performed using a 25-genes signature composed of genes positively enriched in the non-B, stromal sub-compartments, for the first time achieving DZ/LZ discrimination based on stromal/immune features. The report offers new insight into the GC microenvironment, hinting at a DZ microenvironment of origin in DH lymphomas.